Modelling patch mosaic connectivity and ecological corridors with GraphScape. (December 2020) - Pomianowski, Wojciech; Solon, Jerzy
Abstract: Out of many approaches to landscape connectivity, we choose patch-mosaic, flow-neutral framework for modelling. Our new software system GraphScape transforms a vector mosaic map into landscape graph, finds shortest paths and combines them into minimum spanning tree. The result is an optimal network of connections for a given set of patches. To capture mobile agent properties, we use two types of resistance assigned to patches and transfer resistance assigned to combinations of patch classes. Another alternative is step-model, when transfers occur as if on unweighted graph. Resulting MST is rendered by linear skeleton (binary), Transit Density measure assignable to patches (continuous), and summary statistics. A novelty is compete workflow from vector-based map to complex graph structures. We describe concepts and operation of software. GraphScape can be used for ecological corridors planning, identification of key areas of corridors overlap, identification of the role of particular mobility factors, assessment of patch isolation. Highlights: GraphScape is standalone, GUI-based software for modelling patch mosaic connectivity. Input data is vector-based patch-mosaic map. Mobility is modelled by patch resistance and patch-to-patch transfer resistance. Resulting minimum spanning tree is captured by transit density measure per patch.